Banhabaekchulchunma-tang and chongsanggeontong-tang (herbal medicine) effect on migraine: A protocol for a systematic review of controlled trials. Issue 11 (March 2018) - Seo, Jihye; Kim, Cheol hyun; Chu, Hongmin; Moon, Yeonju; Lee, Sangkwan
Abstract: Background: Migraine is a common disease of primary headache, which it causes many kinds of secondary diseases or symptoms. The treatment drugs have sometimes shown side effects such as overuse headache, stroke, and cardiovascular disease. Therefore, the demand for complementary and alternative interventions for migraine has increased. Herbal medicines are a representative intervention to treat migraine traditionally. Among these herbal medicines, Banhabaekchulchunma-tang (BBT) and Chongsanggeontong-tang (CGT) have been most commonly used for migraine treatment in traditional clinical practice. However, to our knowledge, there has been no systematic review considering the efficacy and safety of BBT or CGT on migraine. This protocol aims to perform a systematic review for assessing the effectiveness and safety of BBT or CGT on Migraine. Methods: This protocol was developed according to the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocol (PRISMA-P) and registered on the international prospective register of systematic reviews (PROSPERO). The randomized controlled clinical trials of BBT or CGT for migraine treatment will be searched in following 8 databases from their inception to December 2016: Medline, EMBASE, the Cochrane Central Register of Controlled Trials, OASIS, the Korean Traditional Knowledge Portal, the Korean Medical Database, DBPIA, and the China National Knowledge Infrastructure. Study selection, data extraction, assessment with risk of bias, and data analysis will be performed in order. In this study, headache pain intensity and the total treatment effective rate will be evaluated as primary outcomes. Results and Conclusion: we propose the current protocol to evaluate the effectiveness and safety of BBT or CGT for migraine systematically. Ethics and dissemination: This systematic review will not need ethical approval, because it does not involve human beings. We will publish this systematic review electronically in a peer-reviewed journal. Systematic review registration: PROSPERO CRD42018076171 for BBT and CRD42018085130 for CGT